(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Urinary incontinence (UI) is a highly prevalent and burdensome condition among women.However,fewer than half of women with symptoms consult with a physician about incontinence, and determinant of treatment seeking are not well understood. Objectives: The aim of this study was to determine the prevalence, awareness and determinants of urinary incontinence (UI) among women attending GOPD in BSMMU and the sociodemographic factors involved in their health care-seeking behaviour. Methods: Cross-sectional study was carried out in Gynaeout patient department of Bangabandhu Sheikh Mujib Medical University with a sample of 800 women aged 45 yrs and above. Results: A total of 1000 women were recruited for the study by purposive sampling,among them 800 agreed to participate and completed the questionnaire. Of these, 165 (20.6%) were found to have UL Overall, the reason for not seeking medical attention was mainly embarrassment (40.6%) at having to speak with doctor. Of the total study sample, 566 subjects (70.6%) believed that UI was abnormal and worth reporting to a doctor. Coping mechanisms among incontinent women included frequent washing (58.3%) and wearing a protective perineal pad (42.4%), changing underwear frequently (41.3%), decreasing fluid intake (19.8%) and stopping all work (4.9%). Sufferers were most troubled by their inability to pray (64%) maintain marital relationship (47%), limitation of their social activities (20%), difficulty in doing housework (14%) and inconvenience during shopping (13%). Most (56%) found it most embarrassing to discuss UI with their husbands. The majority of women (51.9%) believed child birth to be the major cause ofUI, followed by ageing (49.5%), menopause (34.2%) and paralysis (25.3%). Most of the subjects (62.3%) believe that UI can cause infection, some (20.5%) believe that it can cause skin allergy and very few think that it can cause cancer or other disorders. Conclusions: Our findings indicate that although UI is relatively common ,it is undereported by the women because of social and cultural attitudes. This findings suggest that strategies to promote care-seeking for incontinence must be developed and employed in the community.